(untitled) (American Journal of Islam and Society, 2019)
The intellectual legacy of Ibn Khaldūn is unique among Muslim historians, and yet he is not fully appreciated in the East. Many Muslim scholars—including Muhammad Abdullah Enan, Muhsin Mahdi, and Mahmoud Dhaoudi—have written about Ibn Khaldūn in English. Their treatment of him was either comparative or historical, but none presented his theory as a valid framework for sociological analysis today as Syed Farid Alatas does in his Applying Ibn Khaldūn.